Intervención de enfermería frente al desconocimiento de enfermedades en familiares de pacientes críticos desde la teoría de Merle Mishel - Amaguaña Supe, Evelyn Lissette (2025)
Background: Nursing staff are characterized by their versatility, providing care with great sensitivity to the human treatment of critically ill patients. It is important to consider that the duty of nursing is not only to care for the patient but also for their family. Hospitalized patients feel supported when they receive visits from a family member, contributing to a decent recovery outcome. Additionally, family members expect nurses to offer emotional support and to understand the fact that they often do not know about the illness affecting their loved one, which causes uncertainty. Methods: This article is based on research with a qualitative paradigm through a systematic review, using an analytical-documentary and retrospective technique. A thorough review and analysis were conducted using national and international databases such as Revista Scielo, the Virtual Health Library, Google Scholar, among others. Results: Healthcare professionals who are working in the intensive care unit consider family to be an essential part in the care process, as they contribute to the patient’s prompt recovery and reintegration into society. Conclusions: Nursing staff have the responsibility of developing care plans to address the needs of both patients and their families. This means finding ways to allow every patient admitted to the ICU to receive visits from their family members, thereby providing holistic care.